Polycentricity in a developing world: A micro-regional analysis for morphological polycentricity in Turkey - Sat, N. Aydan (GeoScape, 2018)
Following the publication of ‘European Spatial Development Perspective’ in 1999, a large number of theoretical and empirical studies have been carried out on polycentric spatial development especially in European settlements. The relationship between polycentricity and economic competitiveness, environmental sustainability and social cohesion are some of the main concerns of these studies. This study aims to clarify ‘the meaning of polycentricity’ in the case of Turkey, as a developing country and analyse the relationship between polycentric spatial development and economic competitiveness, environmental sustainability and social cohesion. After calculation of morphological polycentricity of the regions at NUTS-5 level, the propositions on the positive effects of polycentric spatial development on economic competitiveness, environmental sustainability and social cohesion is tested by using Pearson correlation and OLS regression models. The results of the empirical study are mixed for these three subjects. Polycentric spatial development has not positive effects on economic competitiveness and social cohesion in Turkey case. Conversely, a positive effect exists in terms of environmental sustainability. It can be said, that to reach those policy aims highlighted by European Spatial Development Perspective, could not be realised by only taken into account polycentric spatial development in Turkey case.